Interoperability in health systems: a study of health information models of the National Health Data Network in Brazil (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The National Health Data Network (RNDS) constitutes an advanced interoperability platform designed to promote the integration and efficient exchange of health information between different systems. In this scenario, this work aims to identify the health information models of Brazil's National Health Data Network (RNDS) as a way of promoting interoperability between health systems. Methodologically, a documentary and bibliographic review was adopted. The results show that the RNDS, using standards such as FHIR, and information models to provide interoperability. It is concluded that the RNDS is crucial for a more efficient and interconnected health system.
Keywords: interoperability; health systems; information models; RNDS